Numerical Analysis of the Laser Forming Process of Cylindrical Surfaces - Monsalve-Gonzalez, A; Garcia-Herrera, C; Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This research reports on numerical simulations of the multi-pass laser forming process aimed at obtaining cylindrical surfaces from planar AISI 304 stainless-steel sheets. The effect of laser power, scanning speed, and distance between irradiation lines on the thermomechanical material response is assessed, with particular emphasis on the final curvature radius, maximum temperature, and final plastic deformation. To this end, a coupled thermomechanical finite element formulation is applied to the analysis of different experimental tests reported in the literature. The predictive capabilities of this model are demonstrated in the analysis of bent parts exhibiting a wide range of curvature radii, whose values were found in this work to inversely correlate with the total line energy input to the workpiece. In such situations, it was found that both the thermal response and the effective plastic strain values obtained in each test correlate directly with the line energy value. Furthermore, the distance between irradiation lines was identified as a key parameter in the formation of cylindrical surfaces, as it significantly influences the displacement and induced deformation. However, no significant impact of this parameter on the effective plastic strain was observed. © 2025 by the authors.